Overexpression of Arabidopsis H+-pyrophosphatase improves the growth of alfalfa under long-term salinity, drought conditions and phosphate deficiency - Jia-Hao Su; Tian-Hui Bai; Fei Wang; Ai-Ke Bao (Czech Journal of Genetics and Plant Breeding, 2019)
Alfalfa planting is threatened by limited arable land, salinization, water shortage, and soil nutrient deprivation. To deal with this challenge, we previously introduced the Arabidopsis type I H+-pyrophosphatase gene AVP1 into alfalfa and found that transgenic lines exhibited enhanced tolerance to short-term salinity or drought. In this study, the growth performances of two transgenic lines were further investigated under long-term salinity or drought conditions, as well as under phosphate deficiency (low-Pi). Compared with wild-type (WT) plants, the transgenic alfalfa showed better growth performance with taller plants and more biomass accumulation after being treated with either long-term salinity, long-term drought, or low-Pi. Most importantly, the overexpression of AVP1 significantly increased the root dry weight and the root/shoot ratio of transgenic alfalfa. A more robust root system facilitates the transgenic alfalfa to absorb nutrients, and in turn promotes the growth of the plants. Whether being treated with low-Pi or not, transgenic plants showed higher total phosphorus concentrations by 16.5-35.5% than WT plants. This study laid a foundation for breeding alfalfa cultivars adapted to saline, arid and nutrient-deprived marginal land.